2021
DOI: 10.3390/molecules26102976
|View full text |Cite
|
Sign up to set email alerts
|

Activity of Experimental Mouthwashes and Gels Containing DNA-RNA and Bioactive Molecules against the Oxidative Stress of Oral Soft Tissues: The Importance of Formulations. A Bioreactor-Based Reconstituted Human Oral Epithelium Model

Abstract: Background: DNA-RNA compounds have shown promising protection against cell oxidative stress. This study aimed to assess the cytotoxicity, protective, or preventive effect of different experimental formulations on oral epithelia’s oxidative stress in vitro. Methods: Reconstituted human oral epithelia (RHOE) were grown air-lifted in a continuous-flow bioreactor. Mouthwashes and gels containing DNA-RNA compounds and other bioactive molecules were tested on a model of oxidative stress generated by hydrogen peroxid… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 56 publications
0
1
0
Order By: Relevance
“…The mouth chronic diseases are able to produce an unbalanced relationship between these exogenous agents and the physiological mechanisms for damage repair [ 27 , 28 , 29 ]. Several studies demonstrated that the hydrolyzed DNA is able to absolve a protective agent against the oxidative stress in the oral environment [ 21 , 30 ]. Moreover, this component presents a high versatility and could be combined with anti-microbial agents (chlorhexidine, essential oils) in form of topical gels and mouthwash solution [ 6 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…The mouth chronic diseases are able to produce an unbalanced relationship between these exogenous agents and the physiological mechanisms for damage repair [ 27 , 28 , 29 ]. Several studies demonstrated that the hydrolyzed DNA is able to absolve a protective agent against the oxidative stress in the oral environment [ 21 , 30 ]. Moreover, this component presents a high versatility and could be combined with anti-microbial agents (chlorhexidine, essential oils) in form of topical gels and mouthwash solution [ 6 , 18 ].…”
Section: Discussionmentioning
confidence: 99%